Adapted physical education activities for the socially-alienated primary school children - Musin, Erlinda Zamora 1941-; Santiago, Bernarda Pretencio (1972)
The purposes of the study were to adapt physical education activities for the socially-alienated children in the primary level, to understand the values derived from the adapted physical education activities, and to focus attention to and interest in the physical education of the socially-alienated children. The study aimed to show the importance of a well-planned physical education program. Activities selected fall on six categories: games of low-organization, classroom games, rhythm and dance, social recreation, story plays and self-testing activities and stunts. These six aspects are subdivided to help the teacher know the values for all these activities.
"March, 1972."
Vita.
Thesis (Master of Arts in Teaching - Special Education : Behavior Problems)--University of the Philippines, Diliman.
Keywords: Physical education and training -- Study and teaching (Primary) -- Philippines; Children with social disabilities -- Education (Primary) -- Philippines; Activity programs in education -- Philippines